The Interactive Bahasa Indonesia Learning Module Innovation for the Basic Education Level in the Global Computation Era - Wirnita Wirnita; Nirwansyah Nirwansyah (Universitas Jambi, Indonesia, 2022)
This research aimed to produce Bahasa Indonesia learning modules to achieve educational goals efficiently and effectively. It was Research and Development (R & D) proposed by Trianto (2009) with procedural implementation up to 3D, which consisted of the define stage, design stage, and development stage. The validators of the questionnaire were three expert lecturers. Furthermore, the effectiveness test was the test result of the class IVB students at SDN 03 Alai Padang, while the practicality test was carried out on teachers and students. The limited-scale module trial stage was carried out on five students of class IVA, and the small-scale module test was carried out on 28 students of class IV B. The results showed that the validity test of the resulting module was in the category of very valid with an average value of 91.23% both from the aspect of the content or material feasibility 90% and from the presentation and language 96% and design was 87.70%. The results of the module effectiveness test were in the category of effective (98%). The resulting module practical test was categorized as very practical by the teacher, with an average percentage of 95%, and very practical by students, with an average of 98.2%. The innovation of interactive Bahasa Indonesia learning modules based on science for the basic educational level in the global computing era meets the criteria of valid, practical, and effective. This interactive Bahasa Indonesia learning module based scientific can be used as a learning resource on poetry subjects for fourth-grade students in elementary school.